SOSIALISASI LITERASI KEJAHATAN DUNIA MAYA (CYBER CRIME) PADA GENERASI MILENIAL DI DESA KELAPIAN - Asnawi Asnawi; Lukman Hapidin; Moh Ali Alamsyah; Rama Nugraha; Dewita Sabila; Lisa Ananda Fahreza; Luis Fiska Rahayu (Indonesian Collaboration Journal of Community Services, 2023)
This study aims to assess the effectiveness of cyber crime literacy socialization among the millennial generation in Kelapian Village. As active users of the internet and social media, millennials are exposed to a high risk of cyber crime threats. The research employs survey questionnaires and observation methods to collect data from millennial respondents in Kelapian Village. The findings reveal that while the majority of millennials have a sufficient understanding of cyber crime, some lack awareness of its risks and consequences. The current cyber crime literacy socialization efforts have not fully achieved their objectives. Recommendations to enhance effectiveness include utilizing engaging and interactive methods and actively involving families and schools. This research contributes by providing guidelines to increase awareness and vigilance among millennials concerning cyber crime. It is hoped that implementing these recommendations will enable millennials to better confront cyber threats in the future